2017
DOI: 10.4314/jasem.v21i5.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of spiny pigweed (<i>Amaranthus spinosus</i>) and water leaf (<i>Talinum triangulare</i>) for bioremediation of crude oil polluted soil in Ikarama Community in Bayelsa State Nigeria

Abstract: ABSTRACT:The potential soil amending impact of various concentrations of macerated roots of Amaranthus spinosus and Talinum triangulare singly and in combination on crude oil polluted soil of Ikarama community of Yenagoa in Bayelsa State Nigeria was investigated using gas chromatography technique for twelve weeks. The polluted soil was bagged in seven groups with the addition of 250g of Amaranthus spinosus root, 500g of Amaranthus spinosus root, 250g of Talinum triangulare root, 500g of Talinum triangulare roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The prospect of bioremediation technology in effecting desirable reclamation of polluted environment has been reported by Okoye et al (2017); Sivaramakrishnan et al (2021) coupled with the employment of amaranths for bioremediation studies which Chinmayee et al (2012); Rehaman et al (2020) have submitted to have produced promising results over the years. The ability of suitable organic amendments to facilitate operational reclamation of SEO polluted soil has equally been reported by Osaigbovo et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The prospect of bioremediation technology in effecting desirable reclamation of polluted environment has been reported by Okoye et al (2017); Sivaramakrishnan et al (2021) coupled with the employment of amaranths for bioremediation studies which Chinmayee et al (2012); Rehaman et al (2020) have submitted to have produced promising results over the years. The ability of suitable organic amendments to facilitate operational reclamation of SEO polluted soil has equally been reported by Osaigbovo et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this plant has a potential to be used as plant for phytoremediation. It degrades polycyclic aromatic hydrocarbon and total petroleum hydrocarbon from crude oil polluted soils (Okoye et al, 2017).…”
Section: Phytoremediationmentioning
confidence: 99%
“…The nutraceutical values of amaranths have been reported widely in scientific publications [13,15,21,[43][44][45]. Findings from different experiments have indicated that Amaranthus has a higher proximate composition than commonly consumed food crops, such as corn (Zea mays), buckwheat, rye, and rice [15]; comparable nutritive characteristics to commonly patronized vegetables, e.g., spinach (Spinacia oleracea L.) [31]; equivalent nutrient content to some fodder crops, such as barley, maize, and wheat [46]; and is rich in extremely rare amino acids (e.g., lysine and tryptophan) that could replace animal protein and supplement human diets with moderate-quality amino acids [47,48]. Metabolic diseases, such as diabetes, ulcers, congestive cardiac, liver, and renal failure, cancer, helminthic infections, and most degenerative diseases, such as ageing hypertension, atherosclerosis, obesity, and being chronically underweight are induced by damages done to cells and tissues by free radicals [17,[49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%